Identifying patients suitable for palliative care - a descriptive analysis of enquiries using a Case Management Process Model approach - Kuhn Ulrike (BMC Research Notes, 2012)
Abstract Background In Germany, case management in a palliative care unit was first implemented in 2005 at the Department of Palliative Medicine at the University Hospital Cologne. One of the purposes of this case management is to deal with enquiries from patients and their relatives as well as medical professionals. Using the Case Management Process Model of the Case Management Society of America as a reference, this study analysed (a) how this case management was used by different enquiring groups and (b) how patients were identified for case management and for palliative care services. The first thousand enquiries were analysed considering patient variables, properties of the enquiring persons and the content of the consultations. Results Most enquiries to the case management were made by telephone. The majority of requests regarded patients with oncological disease (84.3 %). The largest enquiring group was composed of patients and relatives (40.8 %), followed by internal professionals of the hospital (36.1 %). Most of the enquiring persons asked for a patient’s admission to the palliative care ward (46.4 %). The second most frequent request was for consultation and advice (30.9 %), followed by requests for the palliative home care service (13.3 %). Frequent reasons for actual admissions were the need for the treatment of pain, the presence of symptoms and the need for nursing care. More than half of the enquiries concerning admission to the palliative care ward were followed by an admission. Conclusions Case management has been made public among the relevant target groups. Case management as described by the Case Management Process Model helps to identify patients likely to benefit from case management and palliative care services. In addition, with the help of case management palliative patients may be allocated to particular health care services.